Stepping into a Critical Crossroads? Analysis of the Current Status and Obstacles of the Introduction of the Deep-Sea Mining Draft Exploitation Regulations, and China's Response - LI Jiaxing (Haiyang Kaifa yu guanli)
Because of the rapid development of deep-sea science and technology, the international community is entering the stage of promoting deep-sea mining in an all-round way. The International Seabed Authority (ISA) is currently responsible for developing rules, regulations and procedures related to deep-sea mining, and the triggering of the two-year rule in Nauru in 2021 has made it necessary for the ISA to accelerate its institutional development. However, due to the influence of various interests, the discussion around the deep-sea mining management system has become the focus of controversy, and there are more than 30 institutional issues unresolved, resulting in the failure of the Deep-Sea Mining Draft Exploitation regulations to be adopted as scheduled. As an important participant and contributor to the development of the international seabed area, China should help improve the existing deep-sea resource development system, strengthen deep-sea scientific research, improve deep-sea resource development capacity, actively build a blue partnership for deep-sea mining, and assist the International Seabed Authority in promoting the construction of deep-sea mining system.